Organization and management : a critical text - Barry, Jim; . (London : Thomson Learning, 2000)
Unsettling orthodoxy. Organizational lives. The limitations of management. The politics of organization and management.
Keywords: Economics; Management; Organization; Organizational behavior; Organization; Management